Total quality management in the context of University 4.0: New game new rules - Ülker, Nilüfer (Frontiers in Education, 2023)
There have been many changes in the field of higher education in accordance with the advancements brought by the new industrial era, which is defined as Industry 4.0. Introduction of Industry 4.0 has definitely influenced ongoing practices requiring alignment and adaptations in many spheres of higher education including but not limited to Total Quality Management (TQM). As a TQM system, ISO 21001 has been specifically designed and developed to serve to the needs of educational institutions, in this particular case universities. Considering the rate of advancements in the context of Industry 4.0 where previously defined rules and policies no longer apply, universities have an important role in revising and improving their current practices in TQM accordingly to maintain their quality in this competitive environment. To be successful in the new game with new rules, this paper will provide a framework for higher education institutions for successful implementation of TQM, particularly ISO 21001, in line with the essentials of University 4.0 through alignment of ISO 21001 principles with University 4.0 practices to contribute to quality and competitive advantage of universities under current circumstances.